In Situ Grown CoMn2O4 3D‐Tetragons on Carbon Cloth: Flexible Electrodes for Efficient Rechargeable Zinc–Air Battery Powered Water Splitting Systems (Small 47/2021). Issue 47 (25th November 2021) - Janani, Gnanaprakasam; Surendran, Subramani; Choi, Hyeonuk; Han, Mi‐Kyung; Sim, Uk
Abstract : Binder‐Free Flexible Electrodes The integration of energy storage and conversion system envisions promising green energy technologies that ensure the uninterrupted production of sustainable hydrogen energy. In article number 2103613, Uk Sim and co‐workers report their first demonstration of in situ‐grown CoMn2 O4 3D tetragons as a binder‐free flexible multifunctional electrode for a built‐in integrated rechargeable zinc‐air battery‐powered water splitting system.